2021
DOI: 10.1590/s0004-2803.202100000-42
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 and Homocysteine Levels in Patients With Nafld: A Systematic Review and Metanalysis

Abstract: BACKGROUND: The vitamin B12 absorption can be affected in patients with nonalcoholic fatty liver disease (NAFLD), and low serum vitamin B12 levels has been related to the high homocysteine (HCY) levels and to the degree of NAFLD. OBJECTIVE: To carry out a systematic review and metanalysis of serum vitamin B12 and HCY levels in patients with NAFLD. METHODS: Original studies including serum vitamin B12 and HCY levels in humans with NAFLD were included. The searches were performed in four databases. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…Serum vitamin B12 and folate levels were not associated with NAFLD or advanced fibrosis. Consistently, a meta-analysis showed that vitamin B12 levels were similar between participants with and without NAFLD [6]. Serum vitamin B12 and folate were affected by many factors, such as age, dietary habits, and lifestyle.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Serum vitamin B12 and folate levels were not associated with NAFLD or advanced fibrosis. Consistently, a meta-analysis showed that vitamin B12 levels were similar between participants with and without NAFLD [6]. Serum vitamin B12 and folate were affected by many factors, such as age, dietary habits, and lifestyle.…”
Section: Discussionmentioning
confidence: 72%
“…Our study suggested that HCY was independently associated with the risk of advanced fibrosis in NAFLD. It was demonstrated that HCY was increased in participants with histology-confirmed NAFLD [ 6 , 10 ]. In a sizeable Chinese epidemiological study, HCY was associated with NAFLD diagnosed by ultrasound [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bazı çalışmalarda NAYKH hastalarında kontrollere kıyasla serum B12 seviyelerinin azaldığı (47,49), düşük vitamin seviyelerinin ise daha yüksek fibrozis derecesi ile ilişkili olduğu bulunmuştur (45). Meta analiz ve sistematik derleme çalışmasında ise B12 vitamini seviyelerinin NAYKH ile ilişkili olmadığı, ancak vakalarda homosistein seviyelerinin anlamlı şekilde daha yüksek olduğu bildirilmiştir (52). Bu çelişkili sonuçlara rağmen NAYKH'nin daha iyi yönetimi için hastaların B12 vitamin seviyelerinin takip edilip eksiklik olduğunda düzeltilmesi önerilmektedir (49).…”
Section: B12 Vitaminiunclassified